Tuesday, August 23, 2011

WS7

Quadratic expression
2x^2 +2
x^2+2x+1
=(x+1)^2
ax^2 +bx+c


Linear Expression
ax+b eg 2x, 2x+2
y=2x
f(x)=2x


Quadratic expressions on the first page:
(i)x^2 -6x+5 (iii)m^2 (v)(x+3)^2 (vi)2x^2 +1 (viii)(z-2)^2 +z-2 (x)(2x-1)(2x+1)


Example 1:
Factorise x^2 +3x+2

x^2 +3x+2
=x^2 +x+2x+2
=x(x+1)+2(x+1)
=(x+1)(x+2)
Another method:


Example 2:
Factorise x^2 +5x+6

x^2+5x+6
=x^2+3x+2x+6
=x(x+2)+3(x+2)
=(x+3)(x+2)

Example 3:
Factorise y^2 -12y+35
y^2 -12y+35
=y^2 -5y-7y+35
=y(y-5)+7(y-5)
=(y-5)(y-7)

Example 4:
Factorise a^2 -5a-14
a^2 -5a-14
=a^2 +2a-7a-14
=a(a+2)-7(a+2)
=(a-2)(a-7)


©®™Mr Johari

No comments:

Post a Comment